PERILAKU MERUSAK LINGKUNGAN HIDUP: PERSPEKTIF INDIVIDU, ORGANISASI DAN INSTITUSIONAL - Dermawan, Mohammad Kemal (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
A wide variety of indicators suggest that humans are destroyingthe earth at a rapid rate. Forests, air, water, human health, andendangered species are all in trouble. Overall, humans arecreating economic growth by depreciating the capital in naturalresources that allows for that growth. We argue that the lens oforganizational behavior yields insights not otherwise visible toexplain this behavior. We provide a multi-level analysis of thedestructiveness of taken-for-granted belief and behavior. Weconsider (1) how human perception of environmental problemsis affected by cognitive biases; (2) how individuals areinfluenced in these biases by the organizations of which theyarea part; and (3) how institutions persist that guide ourawareness of our connections to the environment.